Do Conditionalities Increase Support for Government Transfers?. Issue 3 (3rd March 2020) - Zucco, Cesar; Luna, Juan Pablo; Baykal, O. Gokce
Abstract: Conditional Cash Transfers (CCTs) have spread through the developing world in the past two decades. It is often assumed that CCTs enjoy political support in the population precisely because they impose conditions on beneficiaries. This article employs survey experiments in Brazil and Turkey to determine whether, and in what contexts, making government transfers conditional on behaviour of beneficiaries increases political support for the programmes. Results show that conditional transfers are only marginally more popular than similar unconditional transfers in nationally representative samples, but that this difference is substantially larger among the better-off and among those primed to think of themselves as different from beneficiaries. These findings imply that conditionalities per se are not as strong a determinant of support for transfers as the literature suggests, but that they can still be helpful in building support for transfers among subsets of the population that are least likely to support them.